2017
DOI: 10.1002/jcp.26131
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional role of ephrin A1‐Eph system in stimulating cell proliferation and protecting cells from cell death through the attenuation of ER stress and inflammatory responses in bovine mammary epithelial cells

Abstract: Structural and functional development of the mammary gland is constant in the mammary gland life cycle. Eph receptors and their ligands, ephrins, control events through cell-to-cell interactions during embryonic development, and adult tissue homeostasis; however, little information on participation of ephrin A1, a representative ligand of the Eph receptor, in the development and function of normal mammary glands is known. In this study, we demonstrated functional effects of the ephrin A1-Eph system and mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 53 publications
(67 reference statements)
1
13
0
Order By: Relevance
“…Previous studies conjectured that regulating ER stress may be important for development of the bovine mammary gland, as the expression of the ER stress component genes changes dynamically in bovine mammary tissue during lactation (Invernizzi et al, 2012). To the best of our best knowledge, along with our previous study, this is the first report of a ligand, CCL2, that attenuates ER stress in bovine mammary epithelial cells (Kang et al, 2017).…”
Section: Discussionsupporting
confidence: 50%
“…Previous studies conjectured that regulating ER stress may be important for development of the bovine mammary gland, as the expression of the ER stress component genes changes dynamically in bovine mammary tissue during lactation (Invernizzi et al, 2012). To the best of our best knowledge, along with our previous study, this is the first report of a ligand, CCL2, that attenuates ER stress in bovine mammary epithelial cells (Kang et al, 2017).…”
Section: Discussionsupporting
confidence: 50%
“…This is supported by reports that the expression of ephrin-B2, EphA2 and ephrin-A1 is increased in cerebellar Purkinje cells of EphA4 knockout mice, which likely compensate for the function of EphA4 in patterning the Purkinje cells compartment 38 . Moreover, members of the Eph/ephrin family are involved in regulation of cell death in the brain, such as ephrin-A1 39 , ephrin-A5, EphA7 40 and EphB2 41 . Recently, Ling and colleagues reported that reduction of mRNA expression of EphA4 in the CNS by antisense oligonucleotides (ASO) did not result in significant improvement in functional performance 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Calcium channel, voltage-dependent, alpha-2/delta subunit 1 (CACNA2D1) gene is considered to be an important noncytokine candidate gene influencing mastitis (Deb et al, 2014). Eph A-ephrin A1 (EPHA1) system is a positive factor in the increase and maintenance of epithelial cells in mammary glands of cows; the signaling system contributes to development, remodeling, and functionality of normal mammary glands and could overcome mastitis in cows and other mammals (Kang et al, 2018). Fc-g receptors (FCGR) play a role in the response to rituximab in autoimmune -receptor III a (FCGR3A) diseases and is a very important factor of immune system (Robledo et al, 2012).…”
Section: Grb10 Calcr Trpv6mentioning
confidence: 99%